Pharmaceutical analysis of denibadiya decoction in survey on treatment line for hemipleagia (pakshaghata) - Kumari, S.M.M.W.; Wickramasinghe, M.R.M.; Herapathdeniya, S.K.M.K. (International Journal of Applied Ayurved Research, 2022)
Complete paralysis of one half of the body called hemiplegia . Stroke is the major consequence of cerebrovascular disease, known as second most common cause of death. Annually, 15 million people worldwide suffer from strokes. Hemiplegia is a condition similarto Pakshaghata. It is one of the Vata Vyadhis. In Ayurveda Nidana Parivarjana, Shodana and Shamana Chikitsa used for treatment line of Pakshaghata.Denibadiya decoction commonly used in traditional system of medicine in Sri Lanka for Pakshaghata.Objectives were, to find out most commonly used decoction in treatment line for Pakshaghata, and to study pharmaceutical analysis of selected decoction.Denibadiya decoction is identified as most commonly used decoctionin survey in Ayurveda teaching Hospital, Borella. According to survey, total 21 types of preparation of drugs used as treatment line of Pakshaghata within 8 weeks. In those preparations; 4 types of Kashaya (19.04%), 3 types of Vati (14.28%), 2 types of Kalka(09.52%), 5 types of Taila (23.80%), 1 type of Leha (04.76%), 1 type of Pattu/Mallum/Plaster (04.76% ) , and 5 types ofChoorna (23.80%) were identified as treatment line. Among the used 4 types of Kashaya the most importantlyDenibadiya used during 6 weeks. Pharmaceutical analysiscompleted for 8 types of ingredients of Denibadiya decoction in DravyagunaVignana Laboratory of Institute of Indigenous Medicine, University of Colombo. According to physical and chemical analysis of 8 types of ingredients of Denibadiya decoction, it can be concluded as observed physical analysis, Foreign matter value (1.58%), Color (brownish red), Odor (pungent), Taste ( Thiktha and Kashaya ), PH value (6.19 ), Moisture content ( 15.44% ), Total ash value (9.025%),Water soluble ash content (6.45%), Acid insoluble ash content (17.75%). According to the observed chemical analysis, Flavonoids, Saponins, Terpenoids, Alkaloids, Glycosides, Carbohydrates, Tannins, Proteins were present except Steroids. Results of Thin Layer Chromatography was done (Rf1- 9.6, Rf2-1.4,Rf3 1.04). It could be recommended that statistical analysis of revealed data and efficacy of Denibadiya decoction will be evaluated in further clinical study for treatment according to progress of the patients of Pakshaghataas continuation of this study.
Keywords: Pakshaghata; Denibadiya decoction; Pharmaceutical analysis